O fluxo do conhecimento e a expatriação em negócios internacionais - Francisco, Pedro de Aguiar Bego (2019)
According to leading experts in international business, the competitive advantage of multinationals depends on their ability to acquire and transfer knowledge across borders. Knowledge can be transferred by the parent to the subsidiary (or vice versa), and from one subsidiary to another. Achieving an efficient knowledge transfer is the underlying goal of expatriates in multinational companies. Although several researchers have addressed the purpose of expatriation, no research has been conducted to understand how multinational companies' knowledge flow strategies influence the direction, extent, duration or purpose of expatriation. A comprehensive search in the international business literature and human resource management has resulted in the identification of the research problem. A theoretical framework was developed to examine the relationship between the MNC strategy, the knowledge flow strategy, the use of expatriates, and the purposes of expatriation. The methodology has a quantitative approach, through a survey applied to expatriate employees in MNCs subsidiaries, regardless of location. There were 87 respondents who completed the questionnaire integrally, being the sample used in the study. The collected data was interpreted through analysis of variance and comparison of means (ANOVA). Because the sample is too small, and therefore the statistical tests are not so expressive, it was decided to interview 5 notorious professionals with many years of experience in the field of expatriation. After analyzing and discussing the data, the research results revealed that different strategic functions of the subsidiaries imply different strategies of knowledge flow, leading to different expatriation purposes (strategic, operational and learning). Global innovative subsidiaries receive expatriates for all three purposes. The integrated players do not demonstrate an affinity with the strategic purpose, only with operational and learning. Implementing subsidiaries receive expatriates for learning and strategic purposes. And local innovative, do not present significant results for the use of expatriates. The study also provides evidence of a relationship between the duration of expatriations and the different purposes of expatriation. The duration for strategic and operational purposes is two to three years, while the duration for learning is about one to two years. Other factors such as the expatriate's learning cycle and the ability of local employees to absorb knowledge were identified as possible drivers of the duration.